Removal of methylene blue From Aqueous Solution Using Lemon Peel - Fe3O4 Nanocomposite Adsorbent - Ameera Nasser; Sabreen Kareem (Wasit Journal of Engineering Sciences)
In this study, nanocomposite from the lemon peel was synthesized after precipitation nano iron oxides (LE-Fe3O4) by co-precipitation method and used as an important adsorbent in the adsorption process to remove the MB Dye from the aqueous solution in the batch study taking into account the parameters (pH, dose, initial concentration, and contact time). The optimum condition obtained from the experiment appears to be pH 8, 15mg\50ml dose, 50 ppm initial MB concentration, and 40 min contact time. Max adsorption capacity was  80 mg/g, and the adsorption experimental data best fitted with  langmuir isotherm model indicating that the adsorption was monolayer.